Kebijakan Pajak dalam Indonesia Coretax : Studi Perbandingan dengan Sistem Perpajakan di Malaysia - Gunawan Widjaja; Songga Aurora Abadi; Mervyn Mervyn (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Taxation contributes to national development, and Indonesia has responded to global dynamics by introducing Indonesia Core Tax, a digital system designed to improve tax transparency and compliance. Although Indonesia has adopted various digital systems such as e-Faktur and e-Invoicing, it still faces implementation challenges, while Malaysia is more advanced with its integrated and phased API-based e-Invois system. This study examines taxation policy within the framework of Indonesia Core Tax, focusing on the legal aspects of e-Invoicing implementation as part of the digital transformation of tax administration. The analysis covers the hierarchy and functions of legislation, from laws and regulations to Minister of Finance regulations (PMK) and technical regulations of the Directorate General of Taxes (DJP). This study uses a normative legal research method with a legislative approach and a comparative approach to compare Indonesia's digital taxation system with Malaysia's, covering legal structure, legal substance, and legal culture. The results of the study show that although Indonesia has a fairly complete digital legal framework, the implementation of the e-Invoicing system still faces challenges in terms of regulatory consistency and technological readiness. In contrast, Malaysia has already implemented a mandatory and centralized API-based e-Invoice system through a clearance model approach. This study recommends harmonizing digitalization policies in taxation and strengthening the legal system as strategic steps toward more effective and adaptive tax administration.